Mechanisms of metastatic bone disease - target for modern treatment - Szczylik, Cezary; Z. Pawlak, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2002)
Bone is the third most common organ subject to by cancer metastases. Breast, prostate, lung and renal cancers metastasize to the bone most frequently. The results of metastatic bone disease treatment are better in comparison to metastases developed in other organs. It is possible by dint of understanding the molecular and cellular mechanisms specially involved in metastases to the bones. The initial stages of metastases formation are similar in tumors with different localization. However, bone invasion is dependent on the imbalance between osteoblast and osteoclast function. Direct destruction of bone by cancer cells is not very important. Activated osteoclasts play a pivotal role in both osteolytic, and initial steps of osteoblasic metastases. There are several most important factors involved in the osteoclast activation in-patients with neoplasia: parathyroid hormone-related protein (PTHrP), interleukin-1 (IL-1), interleukin-6 (IL-6), receptor activator of NF-kappaB ligand (RANKL), and macrophage inflammatory protein-1-alpha (MIP-1a). RANKL activity can be blocked by osteoprotegerin (OPG), its soluble decoy receptor. Several positive feedbacks are made in developed bone metastases: cancer cells secrete osteoclast-activating factors that induce bone resorption, while increased bone resorption releases growth factors enhancing tumor growth. The disruption of this "vicious cycle" is the condition of successful treatment of patients with the metastatic bone disease. Bisphosphonates are the first drugs, which specifically block cellular signaling mechanisms involved in the cancer-induced bone disease.